2013
DOI: 10.3390/ijerph110100507
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phthalate Migration to Food Simulants in Plastic Containers during Microwave Operations

Abstract: Phthalates used as plasticizers in the manufacture of household containers can potentially be transferred to foods that are stored or heated in these plastic containers. Phthalates are endocrine disruptor compounds (EDC) and are found in very low concentrations in foods, thus, highly sensitive analytical techniques are required for their quantification. This study describes the application of a new method developed for analyzing the migration of dibutylphthalate (DBP) and benzylbutylphthalate (BBP) from plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 33 publications
3
37
1
Order By: Relevance
“…The phthalates were determined using a solid-phase microextraction fibre cooled by liquid nitrogen (CF-SPME), as described in Moreira, Andre, and Cardeal (2014). The efficiency of the cooling system was evaluated through the simultaneous analysis of DBP and BBP phthalates by DI-CF-SPME and DI-SPME.…”
Section: Spme Methodsmentioning
confidence: 99%
“…The phthalates were determined using a solid-phase microextraction fibre cooled by liquid nitrogen (CF-SPME), as described in Moreira, Andre, and Cardeal (2014). The efficiency of the cooling system was evaluated through the simultaneous analysis of DBP and BBP phthalates by DI-CF-SPME and DI-SPME.…”
Section: Spme Methodsmentioning
confidence: 99%
“…The TDI set by the EPA for nine phthalates ranges from 0.02 to 0.8 mg/kg/day orally. The European Food Safety Authority's (EFSA) TDI for phthalates is 0.01 mg/kg/day for DBP, 0.05 mg/kg/day for BBP, and 0.05 mg/kg/day for DEHP (Moreira et al 2013). The US Consumer Product Safety Commission examined target subpopulations (women, infants, toddlers, and children), and for eight phthalates (DEP, DBP, DIBP, BBP, DNOP, DEHP, DINP, and DIDP) found that ingestion of food, beverages, and drugs were the greatest sources of phthalate exposure, rather than children's toys and personal care products (Gennings et al 2014).…”
Section: Plastic Ingredientsmentioning
confidence: 99%
“…When evaluating the migration of phthalates, it is essential to consider the characteristics of the food. Phthalates are lipophilic and are found in higher concentrations in fatty foods (Moreira et al, 2014). In this study, the migration test used 95% ethanol as a food simulant to represent fatty foods (food type III, IV A, V, VII A and IX).…”
Section: Migration Of Di-n-butyl Phthalate Into Food Simulantmentioning
confidence: 99%
“…Various method of extraction of phthalates has been published. During the last few years, several methods were proposed for the determination of phthalates by gas chromatography (GC) preceded by different preconcentration techniques such as cold fiber solid phase micro extraction (CF-SPME) for benzyl butyl phthalate (BBP) and di-butyl phthalate (DBP) analysis on plastic container (Moreira et al, 2014); liquid-liquid extraction (LLE) for dimethyl phthalate (DMP), bis (2-ethylhexyl) phthalate (DEHP), DBP, and BBP on milk samples (Milojkovic et al, 2015); ultrasound assisted solvent extraction (UAE) for all contaminants on paper food packaging such as benzophenone, di-isobutyl phthalate (DIBP) and DBP (Vapenka et al, 2016). Suciu et al (2013) used soxhlet extraction for bisphenol A (BPA), DEHP, nonylphenol mono-ethoxylate (NMP) and nonylphenol diethoxilate (NDP) on recycled paper food packaging.…”
Section: Introductionmentioning
confidence: 99%